PENGARUH DAYA TARIK IKLAN DAN BRAND AMBASSADOR BTS TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA PADA MAHASISWA ILMU KOMUNIKASI 2019 UNIVERSITAS SLAMET RIYADI SURAKARTA: PENGARUH DAYA TARIK IKLAN DAN BRAND AMBASSADOR BTS TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA PADA MAHASISWA ILMU KOMUNIKASI 2019 UNIVERSITAS SLAMET RIYADI SURAKARTA - Indah Amelia, Ria Ardila; Hindra H, Nurnawati; Astuti I, Andri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT This study aims to determine the significance of exposure to the influence of advertisements and BTS brand ambassadors on purchasing decisions on the Tokopedia marketplace for 2019 communication science students at Slamet Riyadi University Surakarta. This type of research is explanatory, with collection by questionnaire. The population in this study were students of the 2019 Slamet Riyadi University Surakarta communication science program totaling 196, while the sample used in this study was 100 respondents. The data analysis technique used multiple linear regression. The results showed that the variables of advertising influence exposure and BTS brand ambassadors had a significant effect on purchasing decisions on the Tokopedia marketplace for 2019 communication science students at Slamet Riyadi University Surakarta. The t test results obtained the value of the tcount of 3.433 with a p-value of 0.001. The t test results obtained a value of tcount of 4.069 with a p value of 0.000. The calculated F value is 9.911 with a p-value of 0.000 <0.05. So it can be concluded that there is a significant effect of exposure to advertising influence (X1) and tokopedia marketplace brand ambassador (X2) on the dependent variable of purchasing decisions (Y). Keywords : Advertising Influence, Brand Ambassador, Purchase Decision.